Beyond Neo-liberalism: Research Policies and Society. The Case of Japan - Alain-Marc Rieu (The Copenhagen Journal of Asian Studies, 2013)
The idea of decoupling is playing a major role in various interpretations of the present systemic crisis. This crisis is understood as an effect of neo-liberal policies, which have revolutionized economic systems since the 1980s. Decoupling indicates a qualitative change in the level of autonomy of the economic sphere in industrial societies. But a new level of differentiation also generates various types of recoupling, new forms of integration, cooperation and regulation recomposing social systems at another level. The goal of this article is first to situate the idea of decoupling within its conceptual complex. Secondly, the ecological constraint is considered the source of this intense differentiation within social systems, which has intensified since the 1970s. Finally, based on the case of Japan, this paper explains why large-scale science and technology policies developed since the 1990s have to be understood as part of a recoupling process, a project to reconstruct and reach a social and economic coherence in the long term. Similar policies are now implemented by all major industrial nations. Such policies have the potential to overcome neo-liberalism's negative effects.